Strategic alliances and knowledge sharing: synergies or silos? - Connell, Julia; Voola, R. (Emerald Publishing Group, 2007)
Purpose – The purpose of this paper is to investigate the influence of a relationship marketing orientation within a strategic alliance (referred to as the Alliance) to determine whether those firms have achieved synergy in knowledge sharing or whether they operate as knowledge silos. Design/methodology/approach – To achieve this aim the paper takes a strategic perspective and proposes a model based on the resource-based view of the firm (RBV) in order to discover whether member firms can move Alliance relationships towards knowledge sharing experienced within long-term and continuing relationships. Findings – The results of this study reveal that intangible assets, such as relationships and knowledge, should be managed by the Alliance with the same care as would be undertaken with tangible assets. Further, the development of a relationship market orientation (RMO) by the Alliance appears to be crucial. Research limitations/implications – A key limitation of this paper could be considered the sample size (although the response rate was high) and geographical location. Practical implications – Implications from the study were that, although information and knowledge were being shared, one area of improvement would be in relation to the depth of knowledge sharing that tended to occur on a superficial basis. Originality/value – The findings are original in terms of knowledge sharing across organizational boundaries. There is currently very little research available that focuses on the influence of an RMO on knowledge sharing within network groups.